Pancytopenia and Hypothyroidism in a Patient With Leukemic Infiltration of the Thyroid as the First Presentation of Acute Lymphoblastic Leukemia. Issue 2 (March 2018) - Mooij, Christiaan F.; van Alfen-van der Velden, Janiëlle A.E.M.; Netea-Maier, Romana T.; ten Broek, Roel; Gotthardt, Martin; Hagleitner, Melanie M.
Abstract : We report the case of a 16-year-old female patient with hypothyroidism, goiter, and pancytopenia. Biopsy of the thyroid showed leukemic infiltration. After confirmation of the diagnosis of B-lymphoblastic leukemia, treatment was started. Histologic follow-up at day 33 and 79 showed no residual signs of leukemic infiltration. Hypothyroidism persisted despite successful antileukemic treatment. Leukemic infiltration of the thyroid should be considered as a differential diagnosis in patients with hypothyroidism, goiter, and pancytopenia. We suggest that follow-up of thyroid function and histology should be incorporated in the follow-up of rare patients with acute lymphoblastic leukemia with thyroid infiltration.